Geo-Statistical Analysis of Meteorological Drought and Recurrence Intervals in the Context of Climate Change Over Extreme Northeastern Region of Nigeria - Abaje, Iliya B. (Tanzania Journal of Science, 2023)
This study examined the occurrence of meteorological drought in the context of climate change over the extreme northeastern region of Nigeria using rainfall and temperature data spanning a period of 60 years (1961-2020) and 40 years (1981-2020), respectively. Linear regression, 5-year moving average and Cramer’s test were used to examine the changes in the rainfall and temperature. Rainfall Anomaly Index was used in depicting periods of different drought intensities in the region. The trend analysis of the climate data revealed that the region has been experiencing increasing rainfall and temperature in recent years. Findings also revealed that the droughts of the 1980s were more severe than the Great Sahelian Droughts of 1968-1973. The year 1987 was the driest in the whole period of study (1961–2020). Contrariwise, about 81% of the region from 2000 to 2020 experienced normal to very wet conditions. The mean probabilities of mild, moderate, and severe droughts in the area were 0.14 (recurrence interval of 8 years), 0.11 (recurrence interval of 11 years), and 0.07 (recurrence interval of 16 years), respectively. This study concludes that the number of drought occurrences has decreased in recent years. Therefore, government policies related to agriculture and water resources development in the area should take into account the increasing rainfall and temperature in recent years. Keywords: Climate Change, Meteorological drought, Rainfall, Recurrence Interval, Severe Drought, Temperature